Electrical Characterization Method for Resonance Performance of Photo-Elastic Modulators - Wei Xiong; Liyang Ou; Xuezhou Chen; Chaobo Li (Optics, 2021)
As a kind of resonant device, the modulation efficiency of the photo-elastic modulator (PEM) is determined by its inherent resonance characteristics, including the resonance frequency and quality factor (Q-factor). The existing methods used to characterize the resonance performance of the PEM are mainly based on the optical method to measure the vibration parameters, but these methods are more complex, have a high cost, and are not able to accurately measure the quality factor. Therefore, this paper proposes an electrical characterization method based on impedance measurement. In this method, an equivalent circuit model for the PEM is established. By measuring the impedance vs. frequency curve of the PEM and using the equivalent circuit model for fitting analysis, we can obtain the parameters of the equivalent circuit model. With these parameters, we can eventually calculate the natural resonance frequency and quality factor. The above method was applied to some commercial PEM products for experimental verification. The experimental results show that this method can accurately measure the natural resonance frequency and quality factor of the PEM, and the error is less than 0.03%.